Ventriculovesical Shunting in a Patient with Leptomeningeal Carcinomatosis: An Alternative to VP Shunts. A Technique Report - Luiz Henrique Vargas de Andrade; João Pedro Motter de Carvalho; Arthur Garani Narciso; Alexandre Rossato Félix; Alisson Fucio; Leonardo Christiaan Welling; Nicolas N. Rabelo; Eberval Gadelha Figueiredo (Brazilian Neurosurgery, 2024)
Leptomeningeal carcinomatosis (LC) is a rare but serious complication when cancer cells infiltrate the meninges. It is most commonly associated with breast cancer, but only 5% of breast cancer patients develop it. Leptomeningeal carcinomatosis typically presents with headaches, mainly due to hydrocephalus, and the diagnosis involves a cytological analysis of cerebrospinal fluid (CSF) and/or magnetic resonance imaging (MRI) scans. The treatment of LC consists of a combination of intra-CSF chemotherapy, systemic therapy, radiation therapy, and/or supportive care, including CSF drainage. In the case herein reported, a technique known as ventriculovesical shunting was performed on a female patient with LC and breast cancer who had hydrocephalus due to this condition. This procedure is not as common as ventriculoperitoneal shunts, which can lead, in this case, to serious complications such as peritoneal carcinomatosis.